2017
DOI: 10.20517/2394-5079.2017.45
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Evo-Dev, a novel hypothesis derived from studies on hepatitis B virus-induced carcinogenesis

Abstract: How to cite this article: Cao GW. Cancer Evo-Dev, a novel hypothesis derived from studies on hepatitis B virus-induced carcinogenesis. Hepatoma Res 2017;3:241-59.Non-resolving inflammation, which may be maintained by infection, pollution, and metabolic stimulants and their interactions with immunogenetic predisposition, provides a fertile field for cancer development. This is strongly evident in hepatocellular carcinoma. Here, the framework of a hypothesis called Cancer Evo-Dev is presented, based on the advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 132 publications
(177 reference statements)
0
8
0
Order By: Relevance
“…Among anti-HBe carriers with advanced CLD, targeting the much lower levels of ccc DNA may not be effective in preventing progression to cirrhosis and HCC, because at this stage, most of the HBx made probably comes from integrated templates. Under these circumstances, ccc DNA may persist in a transcriptionally inactive form, which is consistent with the absence of HBV DNA in the blood, even after treatment with direct acting anti-viral agents or therapy aimed at stimulating immune responses against virus infected cells [101,102]. In fact, early work already pointed out that seroconversion to anti-HBe is sometimes associated with the progression of CLD [103,104], even though later work showed that disease progression was associated with continued replication of HBV DNA carrying one or more mutations in the core gene that blocks production of HBeAg [27].…”
Section: Hbx and Inflammationmentioning
confidence: 78%
“…Among anti-HBe carriers with advanced CLD, targeting the much lower levels of ccc DNA may not be effective in preventing progression to cirrhosis and HCC, because at this stage, most of the HBx made probably comes from integrated templates. Under these circumstances, ccc DNA may persist in a transcriptionally inactive form, which is consistent with the absence of HBV DNA in the blood, even after treatment with direct acting anti-viral agents or therapy aimed at stimulating immune responses against virus infected cells [101,102]. In fact, early work already pointed out that seroconversion to anti-HBe is sometimes associated with the progression of CLD [103,104], even though later work showed that disease progression was associated with continued replication of HBV DNA carrying one or more mutations in the core gene that blocks production of HBeAg [27].…”
Section: Hbx and Inflammationmentioning
confidence: 78%
“…By summarizing evidence from a variety of perspectives, we gradually proposed and modified the theory of Cancer Evo-Dev (12). The framework of this theory is as follows (Figure 1):…”
Section: The Framework and Rationale Of Cancer Evo-devmentioning
confidence: 99%
“…The integration of evolution and developmental biology was termed Evo-Devo [12,13]. In this chapter, we present a scientific theory of Cancer Evolution-Development (Cancer Evo-Dev) based on the current understanding of HBV-HCC [14]. This theoretical hypothesis can provide an evolutionary insight of profiling HCC risk and developing more reasonable predictive and prognostic strategies.…”
Section: Introductionmentioning
confidence: 99%